Innovations in Measurement: Visual Analog Scales and Retrospective Pretest Self-Report Designs - Gorrall, Brittany K. (2016)
The authors discuss limitations of two popular measurement procedures, the Likert scale and conventional pretest-posttest self-report design. Both techniques have limits and yet are often combined, leading to restricted fidelity for measuring change. The authors go on to discuss two innovations in measurement that provide researchers with greater assessment fidelity: Visual analog scales and the retrospective pretest design. Moreover, when used in combination, these innovations measurement techniques provide dramatic increases in the power to detect and quantify change.